Understanding the Public-Private Partnership Performance Estimation Model of Republic of Moldova Regions - Irina CALUGAREANU (Communications of International Proceedings, 2021)
Currently, the Republic of Moldova imports about 95% of its energy resources to cover domestic energy consumption, which leads to increased external vulnerability at the local energy security level. In addition, there is a major dependence on natural gas, as it has a share of over 60% of total energy consumption in the country. Firstly, this situation requires a complete rethinking and the establishment of concrete steps at the national level to reduce Moldova's dependence on natural gas and, secondly, to find viable and sustainable solutions to provide alternative energy resources to local communities. Hence, the initiation of a public-private partnership project by the Republic of Moldova Nisporeni and Ungheni District Councils was justified on the difficulties they face with stakeholders and the lack of sufficient experience of public institutions in collecting raw materials - briquettes and pellets - and distributing them to thermal power stations, along with the management of these stations and their maintenance.The article is dedicated to evaluating the public-private partnership projects for the development of biomass thermal energy infrastructure at the regional level.
Keywords: Public-Private Partnership; Infrastructure; Biomass Resources; Design-Build-Operate-Transfer; Rehabilitation-Operate-Transfer